Complex Right forearm fracture - Alejandro Álvarez López; Sergio Ricardo Soto-Carrasco; Yenima de la Caridad García Lorenzo (Archivo Médico de Camagüey, 2018)
Background: road accidents cause many lesions affecting significantly bone and joints system; the forearm is one of the most involved structures. Objective: to show a clinical case of a patient with a complex fracture of the right forearm and the used treatment modality to ensure functional recovery. Clinical case: a 23 years-old, white man, without illness record who suffer a traffic accident and was taken to emergency room of Orthopedics and Traumatology complaining of pain, swelling and limitation of movement of the right forearm and left ankle which stopped him from movement in the affected areas. Simple imaging examination showed wrist and proximal shaft right radial fracture and left ankle fracture, based on clinical and imaging elements, immediate surgical treatment was indicated to reduce and fix fractures. Conclusions: segmental and open fractures of the forearm associated to ulnar bone lost is a complex fracture. There is no a standard treatment for this condition so external fixation and AO plates achieve acceptable functional results.